Malaysia’s Leadership Role in Asean: An Assessment (Journal of International Studies, 2018)
There has been perpetual controversy regarding the leadership of ASEAN, that is complicated and hitherto been a cause for concern. The largest and most populated country in Southeast Asia is Indonesia, and has been regarded as the de facto leader in ASEAN for its influence to spur progress within the organization. However, this does not undermine the role of the other four founding members of ASEAN, specifically Singapore, Thailand, Philippines and Malaysia. Singapore has been considered the leader of ASEAN in the economic realm, championing and pushing forward economic agendas of the organization and its member-states. Moreover, the Philippines have been a strong advocate in promoting and enhancing the socio-cultural development within the organization. Conversely, the role of Malaysia in ASEAN has been scholarly neglected. This study seeks to fill the gaps by analysing the role of Malaysia in ASEAN since 1967, and propose that Malaysia has had a significant degree of influence within the organisation. By incorporating document analysis, this study presents the findings on Malaysiaâ€™s pivotal role in ASEAN. The results conclude that Malaysia was and is still a key leader in the organization and the country should continue to exercise its prerogative for the benefit of its national interest, in addition to maintaining peace, stability and prosperity in the region.